LINGUACULTURAL UNITS AS AN OBJECTS OF SCIENCE ABOUT LINGUACULTURAL TRANSLATION (Journal of Oriental Studies, 2016)
In this article gathered inferences about linguacultural units and they are considered as a main object of science about linguacultural translation. Science about linguacultural translation  is a new scientific direction, which unifies cultural studies, cultural linguistics and the science of translation. In this research work we have tried to give a new opinion to  linguacultural units.
Keywords: Linguacultural unit; science of translation; cultural studies; cultural linguistics